Support for Tourism Development After The COVID-19 Pandemic: The Mediating Role of Quality of Life - Musdar Muhammad; Fajri Hatim; Nurdin I. Muhammad; Dudi Amarullah (Journal of Business Management, 2025)
The role of local communities is a crucial factor in tourism development, particularly post-COVID-19 pandemic. Within the framework of social exchange theory (SET), this study examines how perceived advantages (both personal and community) affect support for tourism development, with quality of life acting as a mediating factor. A total of 196 empirical data were successfully gathered through the distribution of questionnaires, which were subsequently analyzed using PLS-SEM techniques. The results indicate that perceived benefits (personal and community) positively affect quality of life. The study also revealed that the quality of life has a beneficial impact on the level of support for tourism development. The correlation between perceived advantages (both personal and community) and support for tourism growth is ultimately mediated by quality of life. This research significantly contributes to both practitioners and policymakers in developing sustainable tourism.